AN ADAPTIVE MULTILEVEL WAVELET SOLVER FOR ELLIPTIC EQUATIONS ON AN OPTIMAL SPHERICAL GEODESIC GRID - Mehra, Kevlahan, N.K.-R. M. (Society for Industrial and Applied Mathematics, 2008)
An adaptive multilevel wavelet solver for elliptic equations on an optimal spherical geodesic grid is developed. The method is based on second-generation spherical wavelets on almost uniform optimal spherical geodesic grids. It is an extension of the adaptive multilevel wavelet solver [O. V. Vasilyev and N. K.-R. Kevlahan, J. Comput. Phys., 206 (2005), pp. 412–431] to curved manifolds. Wavelet decomposition is used for grid adaption and interpolation. A hierarchical finite difference scheme based on the wavelet multilevel decomposition is used to approximate the Laplace– Beltrami operator. The optimal spherical geodesic grid [Internat. J. Comput. Geom. Appl., 16 (2006), pp. 75–93] is convergent in terms of local mean curvature and has lower truncation error than conventional spherical geodesic grids. The overall computational complexity of the solver is O(N), where N is the number of grid points after adaptivity. The accuracy and efficiency of the method is demonstrated for the spherical Poisson equation. Although the present paper considers the sphere, the strength of this new method is that it can be extended easily to other curved manifolds by choosing an appropriate coarse approximation and using recursive surface subdivision.
Keywords: lifting scheme; second generation wavelets; partial differential equations; optimal spherical geodesic grid; adaptive grid; numerical method; multigrid method